A Systematic Review of Outcome Measures Assessing Disability Following Upper Extremity Trauma. (July 2017) - Jayakumar, Prakash; Williams, Mark; Ring, David; Lamb, Sarah; Gwilym, Stephen
Abstract : Objectives: To define upper extremity outcome measures focusing on trauma and level of initial psychometric evaluation and to assess methodological quality of relevant patient-reported outcome (PRO) measures. Data Sources: A broad search strategy using PubMed, OVID, CINAHL, and PsycINFO was deployed and reported using PRISMA (PROSPERO: CRD42016046243). Study Selection, Extraction, Synthesis: PRO measures involving orthopedic trauma in their original development were selected and original publications assessed, including psychometric evaluations. Extraction, synthesis, and quality assessment were performed using COSMIN. Results: Of 144 upper extremity outcome measures, the majority were designed for the shoulder, wrist, and hand; 20% (n = 29/144) involved trauma conditions in their initial development, PRO measurements, and psychometric evaluation on introduction. Methodological quality was highly variable. Conclusion: A few PRO measures were originally designed for use in upper extremity trauma. Methodological quality and psychometric evaluation need to improve. This review aims to highlight strengths and weaknesses and guide decision making in this field.